An Assessment of the Effect of Remuneration on the Construction Performances of the Professionals in the Nigerian Building Industry - Awolesi, J.A.B.; Ayedun, C.A. (Mediterranean Journal of Social Sciences, 2012)
Construction professionals are the authors on one hand and co-executors of construction projects on the other,therefore, the quality of the services expected of them in construction project delivery as environmental resource manager is key.This paper investigated whether quality of service of the construction professionals in Nigeria is influenced by the level ofprofessional fees receivable for services rendered hence their resource management role. The determinants of service qualityare identified and their means of evaluation examined using the SERVQUAL; instrument used for measurement of the servicequality on responses got from a set of questionnaires administered on the construction stakeholders comprising of theconstruction clients on one hand and the construction professionals on the other hand in Lagos, Nigeria with a view to assessingthe perception of the clients regarding the quality of services being received from their construction professionals vis-a-visclients expectations. The study revealed that there was no significant relationship between the level of fees paid and the qualityof service rendered by the construction professionals as the result of the analysis of variance between service quality gap andthe various methods of fees paid is not reflected in the service quality of construction professionals.